Trends in United States Mass Fatality Incidents and Recommendations for Medical Examiners and Coroners. Issue 3 (September 2017) - Carroll, Emily; Johnson, Amy; DePaolo, Frank; Adams, Bradley J.; Mazone, Dennis; Sampson, Barbara
It is imperative that medicolegal jurisdictions prepare for the occurrence of a mass fatality incident. Despite the trend to plan for catastrophic and complicated incidents, this analysis of recent mass fatality events seeks to better inform authorities regarding the scale and types of incidents that could potentially impact their jurisdiction. The guidance provided by this study serves as a tool to guide the development of plans, acquisition of appropriate resources, and training of staff. To perform this analysis, data were collected from mass fatality incidents occurring in the United States from January 1, 2000 to December 31, 2016 that resulted in ten or more fatalities. Specific data points were collected for each incident including the date, location, number of fatalities, incident type (e.g., man-made or natural), incident subtype, and description (e.g., mass shooting, hurricane, aviation). A total of 137 incidents fit the criteria for inclusion in the analysis, resulting in a total of 8462 fatalities. The average number of incidents was eight per year during the study period. The analysis demonstrates that most mass fatality incidents (88.8%) result in between ten and 50 fatalities and are variable based on incident type and geographic location. This study includes several large-scale incidents, which as outliers have influenced fatality management operations and preparedness efforts on a national level. In particular, the World Trade Center attack of September 11, 2001 and subsequent remains recovery and identification operations have served to inform the New York City Office of Chief Medical Examiner of the capabilities required to manage a complex, protracted victim identification process involving extensive body fragmentation and commingling. While the World Trade Center attack has been shown to be outside the normal trends of mass fatality incidents, it has nonetheless offered the medicolegal community several invaluable lessons.